Effects of Feeding Poultry Slaughterhouse Byproduct Meal on the Growth Performance, Digestibility, Antioxidant Status and Histological Parameters of Broilers - Ahmed Ali Saleh; Talaat K. El‐Rayes; Mahmoud M. Mousa; Sara Mahmoud Omar; Mohammed Abdelhameed Mohammed Kamal; Rashed A. Alhotan; Elsayed O. Hussein; Branislav Galik; Soha A. H. Farag (Veterinary Medicine and Science)
ABSTRACT A total of 3000 1‐day‐old chicks were randomly assigned to 5 groups with 6 replicates (n = 100). The control group was fed standard diets, whereas the other groups were fed diets containing poultry slaughterhouse meal (PSM) at levels of 50, 75, 100 or 125 kg/t. The results indicated that the group fed 75 kg/t of PSM exhibited greater body weight (BW) and body weight gain (BWG) than the other groups. Enhanced crude protein (CP), calcium and phosphorus digestibility coefficients were observed in the 75 kg/t PSM group. Compared with those in the control group, liver weight was increased, plasma high‐density lipoprotein (HDL) was increased, and low‐density lipoprotein (LDL) was decreased in all the PSM groups. The remaining biochemical parameters showed non‐significant changes, except for the serum albumin and globulin levels, which were significantly lower in the PSM groups, except for the globulin level in the 100 kg group. Moreover, liver malondialdehyde (MDA) content decreased, and catalase (CAT), glutathione peroxidase (GSPx) and superoxide dismutase (SOD) increased in the 75 kg/t PSM group. Mild degenerative changes in hepatocytes were observed, indicating the potential benefits of PSM inclusion. In conclusion, incorporating PSM in broiler diets holds promise for improving the health and productivity of broilers by enhancing the growth performance, digestibility, plasma lipids and antioxidative status of these birds.